THE VALUE OF RELIGIOSITY IN SERAT WIRID HIDAYAT JATI BY RADEN NGABEHI RANGGAWARSITA - Hukamak, Moh Tahrikul; Aziz, Muhammad Ilham; Baqi, Subkhana Adzim (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2024)
This paper examines the values of Religiosity in Serat Wirid Hidayat Jati by Raden Ngabehi Ranggawarsita. In this study, the authors use historical research methods that include heuristic, verification, interpretation, and historiography. While the approach used in this research is historical social approach. Ranggawarsita was born on March 15, 1802, he was a closing poet of the Surakarta court, died on December 24, 1873. He was buried in Palar Village, Surakarta area. One of Ranggawarsita's works was Serat Wirid Hidayat Jati, which contains Islamic values such as monotheism and Sufism. From the value of faith (monotheism) can be seen from the pronunciation of the pronunciation of la ilahailallah which means there is no god but Allah. While the value of morality (Sufism) can be seen from the praise of dzikir to God by ignoring his worldly interests, from the value of Islam can be made as a way of life.